Adsorption Mechanism of Activated Carbon Fibre/Carbon Nanotube Composites for Rhodamine B from Aqueous Solution - Wang1, Liping; Zhang2, Mingyu; Huang3, Zhucheng; Zhao1, Chenxi; Pei1, Xijun (Asian Journal of Chemistry, 2013)
Activated carbon fiber (ACF)/carbon nanotube (CNT) composites were fabricated by chemical vapor deposition and characterized with field emission scanning electron microscope, Fourier transformation infrared spectroscopy, pore size distribution and high resolution transmission electron microscopy. The SEM results showed high density carbon nanotubes were well-distributed on the surface of activated carbon fibers. The total volume, BJH mesopore volume and average pore diameter of ACF/CNT composites were 0.5832 cm3/g, 0.095 cm3/g and 2.0140 nm, respectively, which were greater than those of activated carbon fibers. The adsorption data for rhodamine B were well fitted with Langmuir adsorption isotherm and pseudo-second order kinetics equation. The adsorption rate was controlled by inter-particle diffusion and film diffusion. Because the values of DG were positive and the values of DH and Ea were 15.7 kJ/mol and 0.113 kJ/mol, respectively, the adsorption was suggested non-spontaneous and endothermic physisorption. Hydrogen bond was main adsorption mechanism of ACF/CNT composites for rhodamine B from aqueous solution.